Meningkatkan Komunikasi dan Kolaborasi dengan Interprofessional Education (IPE): A Literature Review - Anwar, Haerul; Rosa, Elsye Maria (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background: The application of educational interprofessional education (IPE) needs to be applied in improving communication and collaboration between health professions to reduce medical errors and improve patient safety.Methods: Literature search on IPE through ScienceDirect, ProQuest, and Pubmed databases with predetermined keywords. Then screening was carried out based on inclusion and exclusion criteria, then analyzed for the feasibility of the article than a review.Results: A total of 13 of the 4,350 articles met the requirements to be analyzed in the current review. All articles provide an outline of research objectives including Testing the trends of IPE and how IPE must be designed and implemented in medicine, the effectiveness of the IPE program and the results or impacts as well as the factors that influence IPE perceptions and learning experiences. How to build interdisciplinary collaboration in a multidisciplinary team. The entire article shows that the application of interprofessional education (IPE) can improve knowledge, skills, behavior, collaboration, communication, and help understand the ideas, roles, and responsibilities of each health profession.Conclusion: Based on the analysis of the articles used as literature shows that IPE learning can increase student self-confidence, coordination (planning), control and calmness (reducing anxiety), and commitment (persistence) in supporting patient-centered care.Â